HUBUNGAN PENGETAHUAN DAN SIKAP IBU MENYUSUI DENGAN PEMBERIAN ASI EKLUSIF DI PUSKESMAS DARUSALAM - Maida Pardosi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Promotion of Exclusive Breastfeeding has actually been active for a long time, but the reality is that government programs have not run as expected. Therefore, the purpose of this study was to determine the relationship between knowledge and attitudes of breastfeeding mothers with exclusive breastfeeding at the Darussalam Health Center in 2020. This type of research is an analytic survey with a cross sectional approach. The total population is 195 breastfeeding mothers who have babies aged 0-6 months at the Darussalam Health Center and a sample of 66 people. Sampling using accidental sampling technique. Collecting data through interviews using a questionnaire. Data processing with editing, coding, scoring, and tabulating processes. Analytical data analysis, presented in univariate data analysis and bivariate data analysis. For bivariate data, analyze the relationship between variables using chi square. The results showed that from 66 breastfeeding mothers there were 48 breastfeeding mothers (72.7%) who gave exclusive breastfeeding, 26 breastfeeding mothers (39.4%) who had sufficient knowledge about exclusive breastfeeding, 53 breastfeeding mothers (80.3%). who have a positive attitude about exclusive breastfeeding. There is no relationship between knowledge of breastfeeding mothers and exclusive breastfeeding, with the results of the chi-square test, X2 count < X2 table (1.4 <5.591) and there is a relationship between the attitudes of breastfeeding mothers and exclusive breastfeeding, with the results of the chi-square test, where X2 count > X2 table (34.72 > 3.841). The conclusion of this study is that the majority of breastfeeding mothers who give exclusive breastfeeding are 48 people, the majority of breastfeeding mothers have sufficient knowledge, 26 people, and the majority of breastfeeding mothers have a positive attitude 53 people. There is no relationship between knowledge of breastfeeding mothers and exclusive breastfeeding and there is a relationship between attitudes of breastfeeding mothers and exclusive breastfeeding. It is hoped that breastfeeding mothers and the community can improve attitudes in giving exclusive breastfeeding.